Influence of Contrast Administration on Computed Tomography–Based Analysis of Visceral Adipose and Skeletal Muscle Tissue in Clear Cell Renal Cell Carcinoma. Issue 7 (19th January 2018) - Paris, Michael T.; Furberg, Helena F.; Petruzella, Stacey; Akin, Oguz; Hötker, Andreas M.; Mourtzakis, Marina
Abstract: Background: Computed tomography (CT) scans are being utilized to examine the influence of skeletal muscle and visceral adipose quantity and quality on health‐related outcomes in clinical populations. However, little is known about the influence of contrast administration on these parameters. Methods: Precontrast, arterial, and 3‐minute postcontrast CT images of 45 patients with clear cell renal cell carcinoma were downloaded from The Cancer Imaging Archive and retrospectively analyzed for visceral adipose cross‐sectional area (CSA) and density, and muscle CSA and density at the third lumbar vertebrae. Low muscle CSA index was defined as ≤38.9 cm 2 /m 2 for women and ≤55.4 cm 2 /m 2 for men. Low muscle density was defined as <41 Hounsfield units (HU) for body mass index (BMI) <24.9 kg/m 2 and <33 HU for BMI ≥25.0 kg/m 2 . Results: In both the arterial and 3‐minute phases, contrast administration decreased visceral adipose CSA (−20.9 and −20.9 cm 2 ; P < .001) and increased visceral adipose density (4.8 and 5.8 HU; P < .001), relative to precontrast images. Muscle CSA index marginally increased in the arterial (0.6 cm 2 /m 2 ; P = .007) and 3‐minute phases (0.8 cm 2 /m 2 ; P < .001). This likely represents clinically insignificant changes because it does not alter the identification of low muscle CSA (44.4% vs 42.2%; P = 1.00). Skeletal muscle density increased in the arterial (6.4 HU; P < .001) and 3‐minute phases (8.7 HU; P < .001), which altered the identification of low muscle density (6.7% vs 31.1%; P < .001). Conclusions: Future analyses should consider the phase of contrast during CT imaging because it may alter the interpretations of several parameters.